2004
DOI: 10.1074/jbc.m307698200
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic Peroxiredoxin Attenuates The Activation Of Jnk And P38 But Potentiates That Of Erk In Hela Cells Stimulated With Tumor Necrosis Factor-α

Abstract: Tumor necrosis factor-␣ (TNF-␣

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 55 publications
1
59
0
Order By: Relevance
“…It was not possible to examine the effect of Prx II-DN by transient transfection because, in contrast to the situation in stably transfected cells, only a small fraction of the mutant protein molecules was able to form heterodimers with endogenous Prx II. Heterodimerization with endogenous enzyme molecules is the basis of the dominant negative action of the mutant protein (17). Together, these results suggested that PIP 3 accumulates to a greater extent and persists for a longer time in EGF-stimulated cells in which the intracellular concentration of H 2 O 2 is increased.…”
Section: Effect Of Prx II Overexpression On Egf-induced Pip3 Generationmentioning
confidence: 85%
See 2 more Smart Citations
“…It was not possible to examine the effect of Prx II-DN by transient transfection because, in contrast to the situation in stably transfected cells, only a small fraction of the mutant protein molecules was able to form heterodimers with endogenous Prx II. Heterodimerization with endogenous enzyme molecules is the basis of the dominant negative action of the mutant protein (17). Together, these results suggested that PIP 3 accumulates to a greater extent and persists for a longer time in EGF-stimulated cells in which the intracellular concentration of H 2 O 2 is increased.…”
Section: Effect Of Prx II Overexpression On Egf-induced Pip3 Generationmentioning
confidence: 85%
“…NIH 3T3 cells overexpressing human NADPH oxidase 1 (Nox1) were provided by J. D. Lambeth (Emory University School of Medicine, Atlanta) (16). HeLa cells overexpressing wild-type or a dominant negative mutant (DN) of human Prx II were described previously (17). HeLa and NIH 3T3 cells were grown under an atmosphere of 5% CO 2 at 37°C in DMEM supplemented with 10% FBS, 100 units͞ml penicillin, and 100 units͞ml streptomycin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperoxidized Prxs have been reported to inhibit JNK activities either by removal of hydrogen peroxide (35), or by directly interacting with GSTpi-JNK complex (36). Therefore, Srx may positively regulate JNK activity by maintaining a constant level of reduced Prxs, facilitating the release and activation of JNK from the GSTpi-JNK complex (36).…”
Section: Discussionmentioning
confidence: 99%
“…However, the idea that at least some of the GPx-or Prx-type peroxidases could similarly act as sensors for H 2 O 2 , alkyl hydroperoxides, and peroxynitrite in mammals is intriguing in several respects. It would comply with the observation that redox signaling also takes place at physiological H 2 O 2 fluxes; it could explain why in some cases Prxs improve rather than inhibit signaling (75,238), and it finally might help to explain oxidative modification of proteins with SH group reactivities that are simply not competitive enough to occur without enzymatic support (134). Mechanistically, transducing mechanisms analogous to those worked out for peroxidases of yeasts and Kinetoplastida would be straight forward for all 2-Cys Prxs.…”
Section: Sensing and Transducing Proteinsmentioning
confidence: 79%